Đặt $x=\dfrac{a+b}{c}, \quad y=\dfrac{b+c}{a} \Rightarrow z=\dfrac{c+a}{b}$.
Khi đó: $2\sqrt{xy}=2\sqrt{\dfrac{(a+b)(b+c)}{ca}} \le \dfrac{b}{a}+\dfrac{b}{c}+2$.
Tương tự ta có điều phải chứng minh.
Cách làm khác:
Đặt $a=\frac{1}{x+1} ,b=\frac{1}{y+1} , c=\frac{1}{z+1}$
$x+y+z+2=xyz$
$\Leftrightarrow \frac{1}{a}+\frac{1}{b}+\frac{1}{c}-1=(\frac{1}{a-1})(\frac{1}{b-1})(\frac{1}{c-1})$
$\Leftrightarrow a+b+c=1$
Do đó $x=\frac{1}{a}-1=\frac{a+b+c-a}{a}=\frac{b+c}{a}$
Tương tự, $y=\frac{c+a}{b},$ $z=\frac{a+b}{c}$
Vậy $x+y+z+6=\frac{b+c}{a}+\frac{c+a}{b}+\frac{a+b}{c}+6$
$=\frac{a+b}{a}+\frac{c+a}{a}+\frac{b+c}{b}+\frac{a+b}{b}+\frac{b+c}{c}+\frac{c+a}{c}$
$\geq 2(\sqrt{\frac{(b+c)(c+a)}{ab}}+\sqrt{\frac{(c+a)(a+b)}{bc}}+\sqrt{\frac{(a+b)(b+c)}{ca}})$
$=2(\sqrt{xy}+\sqrt{yz}+\sqrt{zx})$
$(?)$